Novel Loss-of-Function Mutations in NPR2 Cause Acromesomelic Dysplasia, Maroteaux Type - Wu, Jing; Wang, Mengru; Jiao, Zhouyang; Dou, Binghua; Li, Bo; Zhang, Jianjiang; Zhang, Haohao; Sun, Yue; Tu, Xin; Kong, Xiangdong; Bai, Ying (Frontiers in Genetics, 2022)
Acromesomelic dysplasia, Maroteaux type (AMDM) is a rare skeletal dysplasia characterized by severe disproportionate short stature, short hands and feet, normal intelligence, and facial dysmorphism. Homozygous or compound heterozygous mutations in the natriuretic peptide receptor 2 (NPR2) gene produce growth-restricted phenotypes. The current study was designed to identify and characterize NPR2 loss-of-function mutations in patients with AMDM and to explore therapeutic responses to recombinant growth hormone (rhGH). NPR2 was sequenced in two Chinese patients with AMDM via next generation sequencing, and in silico structural analysis or transcript analysis of two novel variants was performed to examine putative protein changes. rhGH treatment was started for patient 1. Three NPR2 mutations were identified in two unrelated cases: two compound heterozygous mutations c.1112G>A p.(Arg371Gln) and c.2887+2T>C in patient 1 and a homozygous mutation c.329G>A p.(Arg110His) in patient 2, yielding distinct phenotypes. RNA extracted from peripheral blood cells of patient 1 showed alternatively spliced transcripts not present in control cells. Homology modeling analyses suggested that the c.1112G>A p.(Arg371Gln) mutation disrupted the binding of NPR-B homodimer to its ligand (C-type natriuretic peptide) in the extracellular domain as a result of global allosteric effects on homodimer formation. Thus, c.2887+2T>C and c.1112G>A p.(Arg371Gln) in NPR2 were loss-of-function mutations. Furthermore, rhGH therapy in patient 1 increased the patient’s height by 0.6SDS over 15 months without adversely affecting the trunk-leg proportion. The short-term growth-promoting effect was equivalent to that reported for idiopathic short stature. Overall, our findings broadened the genotypic spectrum of NPR2 mutations in individuals with AMDM and provided insights into the efficacy of rhGH in these patients.